FENOMENA MUTASI ATLET MENJELANG PELAKSANAAN PEKAN OLAHRAGA NASIONAL XVII - Saharuddin Ita (JURNAL OLAHRAGA PAPUA, 2013)
Abstrack: Mutation athlete phenomenon pre PON XVII. Porpuse this research for fine data about mutation athlete phenomenon Pre PON XVII,   the research race  is descriptive research .  subject research is management KONI provinsi, top organization sport propinsi, coach, and athlete whose prepare to PON XVII at Kalimantan timur. Take sampling used quota purposive stratified sampling with technic focus group discussion, questionnaire, and document. Conclusion : (1) athlete mutation pre PON  constitute a phenomenon accomplished fact because domicile, education, job, following wife/husband and parent; (2) mutation  is rightful authority athlete and sport organization must responship; (3) infraction of rule mutation, because athlete or sport organization. Sanction pattern is athlete unallowable appear on PON; (4) prestation at PON not endall to athlete. Mutation must be compensation to  development of relationship for province; (5) mutation  have to impact  athlete prosperity, compensation  to development from province  athlete destination, must can be development to management province, management regency, so this compensation must until to club; (6) athlete mutation have  positif impact to self athlete but not yet to coach.Key word: Mutation Athlete, PON